Grazing exclusion mediates the trade-off between plant diversity and productivity in Leymus chinensis meadows along a chronosequence on the Songnen Plain, China - Yang Gao (Elsevier, 2021)
Grazing exclusion has become an effective approach for restoring the structure and function of natural grassland ecosystems on the Songnen Plain, China. Variations in, and trade-offs between, plant diversity and productivity throughout the restoration processes are critical for understanding the successional mechanisms of vegetation. In this study, we selected five Leymus chinensis meadow sites at different restoration stages (0, 6, 11, 15, and 23 year) to determine the effects of grazing exclusion on the plant community. Grazing exclusion practices substantially changed the plant composition of degraded L. chinensis meadows. Annuals and biennials accounted for the highest proportion (42.8%) at the grazing site (i.e., the 0-year site), whereas perennial rhizome grasses accounted for the highest proportion of plants (67.5%) at the 11-year grazing exclusion site. Plant species diversity decreased and then increased with time since grazing exclusion over the 11 years. Plant height and cover were highest at the 15-year grazing exclusion site. Restoration of the aboveground biomass took longer than that of the belowground biomass. The relative benefits of grazing exclusion for different restoration objectives changed with time, changing from higher greater benefits for diversity to greater benefits for productivity. The 15-year grazing exclusion site had the lowest trade-off index (0.02), indicating a similar benefit for both species diversity and productivity. Considering the changes in plant communities, the trade-off index is a reliable indicator for evaluating the restoration process; therefore, we recommended grazing exclusion for 15 years as a reasonable duration. This study provides important guidelines for maintaining ecosystem structure and function during grazing exclusion grasslands.